1997
DOI: 10.1073/pnas.94.8.4000
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Taxol and radioimmunotherapy with yttrium-90-labeled chimeric L6 antibody: Efficacy and toxicity in breast cancer xenografts

Abstract: Synergistic multimodality therapy is needed for breast cancer. Breast cancer frequently has p53 mutations that result in cells less likely to undergo apoptosis when exposed to DNA damaging therapies. Taxol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 25 publications
5
84
0
Order By: Relevance
“…Numerous papers have been published in the last few years on the potential advantages of treatment with RAIT and chemotherapy. 8,9,53,54 The possibility of combining RAIT with other small molecular-weight therapeutic agents, particularly those that affect tumor vascular biology or those that take advantage of unique aspects of tumor physiology, has become an active and exciting area of research for us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous papers have been published in the last few years on the potential advantages of treatment with RAIT and chemotherapy. 8,9,53,54 The possibility of combining RAIT with other small molecular-weight therapeutic agents, particularly those that affect tumor vascular biology or those that take advantage of unique aspects of tumor physiology, has become an active and exciting area of research for us.…”
Section: Discussionmentioning
confidence: 99%
“…The primary focus has been on the use of chemotherapy with RAIT. 8,9 An alternative combination therapy approach worth considering is the use of RAIT with an agent that is maximally effective within the physiologic environment of tumor tissue.…”
mentioning
confidence: 99%
“…A blood sample of 4 µl was obtained from the tail vein of each mouse, and samples from mice within a group were pooled and diluted 1:10000 in phosphate-buffered saline for red blood cell counts, 1:20 in 3% acetic acid for white blood cell counts and 1:100 in 1% ammonium oxalate for platelet counts. 18) Body weight change of mice was also monitored. Effect of HT on intratumoral distribution of A7 Radioluminograms (autoradiograms) of tumors were obtained to assess the effect of HT on the intratumoral distribution of A7.…”
Section: Methodsmentioning
confidence: 99%
“…6) Therefore, several kinds of strategies have been examined to improve its efficacy, including the use of biological response modifiers to increase tumor targeting of labeled monoclonal antibodies (mAbs), [7][8][9] the use of a pretargeting system to obtain a better therapeutic ratio to normal tissues 10,11) and combination with other therapeutic modalities such as hyperthermia (HT) [12][13][14][15] and chemotherapy. [16][17][18][19][20][21] Our previous study demonstrated that HT enhanced the absorbed dose with 131 I-A7 anti-colorectal cancer mAb to colon cancer xenografts and significantly improved the therapeutic efficacy of RIT.…”
Section: Abstract: Radioimmunotherapy -Local Hyperthermia -Chemothermentioning
confidence: 99%
“…An opinion shared by many is that radioconjugates may be best applied clinically in solid tumors if combined with a chemotherapeutic agent (Wong, 2006). Most combinations examined preclinically have sought to add a chemotherapeutic agent to enhance the effect of a full dose of the radioconjugate (DeNardo et al, 1997b;Crow et al, 2005;Kelly et al, 2006;Masters et al, 2006), whereas others seek to enhance an effective, yet not curative, chemotherapy regimen with a smaller dose of the radioconjugate (Cardillo et al, 2002;Gold et al, 2003) A few phase I clinical trials have examined the former approach in patients with advanced solid tumors. Some treatment regimens used myeloablative radioconjugate doses with the aid of bone marrow or peripheral stem cell support, but without evidence of objective responses (Wong et al, 2003;Forero et al, 2005;Richman et al, 2005;Sharkey et al, 2005b).…”
mentioning
confidence: 99%